Systemic lupus erythematosus in a male patient: presentation of a case - Romaní, Franco (2008)
Systemic lupus erythematosus is a disease that affects women predominantly, with variable manifestations. This is a case report on a young male patient that debuts with lupus arthropathy, variety Jaccoud’s arthropathy. We review the clinical characteristics of lupus in males and the differences with the disease in females.